Effects of Repetitive Transcranial Magnetic Stimulation Combined with Balance Acupuncture Treatment on Sleep Quality and Psychology in Patients after Stroke - YANG Huazhong; CUI Jinlong; FAN Hexin; XIONG Zhonghui; YAO Yuanmian; ZHOU Shasha; CUI Wenxiu; SUN Tianbao (康复学报)
ObjectiveTo observe the clinical effects of repetitive transcranial magnetic stimulation (rTMS) combined with balance acupuncture treatment on sleep quality and psychology in patients after stroke.MethodsA total of 60 patients with post-stroke sleep disorder admitted at Xiangya Boai Rehabilitation Hospital were selected and randomly divided into three groups: rTMS group (psychotherapy+rTMS), balance acupuncture group (psychotherapy+balance acupuncture treatment), and combination group (psychotherapy +rTMS+balance acupuncture), with 20 cases in each group. All patients were treated for 4 weeks. The overall clinical efficacy was assessed at the end of the treatment course. The Pittsburgh sleep quality index (PSQI), Hamilton anxiety scale (HAMA), Hamilton depression rating scale (HAMD) and other indicators before and after treatment were observed as well as serum γ-aminobutyric acid (GABA), 5-hydroxytryptamine (5-HT) level were detected in all patients.ResultsThe total effective rate was 75% (15/20) in the rTMS group, 73.68% (14/19) in the balance acupuncture group, and 100% (20/20) in the combination group. The total effective rate of the combination group was higher than that of the balance acupuncture group or the rTMS group (P<0.05), while there were no significant differences in the total effective rate between the balance acupuncture group and the rTMS group (P>0.05). After 4 weeks of treatment, the PSQI score of the three groups decreased significantly (P<0.05); compared with the balance acupuncture group and the rTMS group, the PSQI score of the combination group was significantly lower (P<0.05); and there were no significant differences in PSQI score between the balance acupuncture group and the rTMS group (P>0.05). After 4 weeks of treatment, the HAMA score of the three groups decreased significantly (P<0.05); compared with the balance acupuncture group and the rTMS group, the HAMA score of the combination group was significantly lower (P<0.05); and there were no significant differe-nces in HAMA score between the balance acupuncture group and the rTMS group (P>0.05). After 4 weeks of treatment, the HAMD score of the three groups decreased significantly (P<0.05); compared with the balance acupuncture group and the rTMS group, the HAMD score of the combination group was significantly lower (P<0.05)；there were no significant differences between the balance acupuncture group and the rTMS group (P>0.05). After 4 weeks of treatment, the serum level of GABA in the three groups increased significantly (P<0.05); compared with the balance acupuncture group and the rTMS group, the level of GABA in the combination group was significantly higher (P<0.05); there were no significant difference between the balance acupuncture group and the rTMS group (P>0.05). After 4 weeks of treatment, the serum level of 5-HT in the three groups increased significantly (P<0.05); compared with the balance acupuncture group and the rTMS group, the level of 5-HT in the combination group was significantly higher (P<0.05); there were no significant difference in 5-HT content between the balance acupuncture group and the rTMS group (P>0.05).ConclusionBoth rTMS and balance acupuncture therapy can improve sleep quality and psychology in patients after stroke. The combined group showed better therapeutic effects than the balance acupuncture group and rTMS group alone, which is conducive to synergistic enhancement and should be recommended for promotion and application.